The Graying of Central America: A Brief Examination of Institutional Rhetoric, Policy, and Practice - Roberth Steven Gutiérrez-Murillo; Gustavo Cezar Wagner Leandro; Eliana Mourges Codoy; Patricia Krieger Grossi (Research on Ageing and Social Policy)
The population of Central America is aging at an accelerated pace, yet the response of governments has been inconsistent and, at times, misguided. To gain a deeper understanding of this issue, we propose a socio-historical overview on the public institutionalization of aging and old age. We employed the principles of Critical Gerontology, with a specific focus on specialized legislation for older adults, to clarify the extent of legal safeguards recognized in each national regulatory framework. The most significant achievement has been the formation of national councils, which are responsible for overseeing and implementing national aging plans, as well as ensuring compliance with the guarantees enshrined in current legislation. While all States have incorporated an institutional standard on aging, the trajectory of their development has been quite divergent, resulting in a series of bureaucratic challenges. In examining the achievements and ongoing challenges, we identify the key rhetorical, policy, and practice elements that typify the public approach, thereby elucidating the characteristics that frame the institutional response among these countries.